Penerokaan gaya hidup penagih dadah: perspektif teori psikologi individu - Harun, Lily Mastura; Ooi, Boon Keat (Universiti Putra Malaysia Press, 2004)
This qualitative case study was conducted to explore the life-styles of drug addicts. The theory of individual psychology introduced by Alfred Adler was used as a theoretical framework to explore the life-styles of drug addicts. Life-styles were assessed through constructs of family constellation, early memories, patterns of dreams, and basic mistakes. Two trainees from the 'Pusat Pemulihan Rakan Sekelompok Amalan Daya Abadi' (PERSADA) were respondents in this case study. Respondent A was in for the first time for rehabilitation and respondent B was a relapse addict. Structured interviews based on the Individual Psychology Interview questionnaire were conducted. The findings showed that the constructs of individual psychology were able to reveal the life-styles of drug addicts, which were much influenced by family factors.